Analisis Kausalitas Tingkat Inflasi dan Nilai Tukar: Pengujian Vector Autoregression - Nata Negara, I Komang Surya; Sukarsa, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 6, Juni 2015 (pp. 608 - 745), 2015)
Exchange rate movements influence wide on various aspects of the economy, including development of price (inflation). This study aims to determine how the causal relationship between the rate of inflation and exchange rates in Indonesia, also to determine model to predict the rate of inflation and exchange rates in Indonesia. The data that used in this research is secondary data start from month January 2001-October 2014. This research  used Vector Autoregression (VAR) approach. The result of Granger causality test shown that no causal relationship between inflation rates and exchange rates. Therefore, based on the result of VAR test, in predicting the inflation rates in the period ahead with the model INFLATION = 2.93845INFLASI (-1). In predicting the future period exchange rate using model KURS = 2.38492 + 16.2205KURS (-1) -3.84268KURS (-2), where inflation influenced by inflation one period before (t-1) and exchange rates influenced by exchange rates one period before (t-1) and exchange rates two period before (t-2).
Keywords: inflation rates, exchange rates, granger causality, Vector Autoregression (VAR)